Education about the importance of infant’s basic immunizations for pregnant and lactating mothers - Wahyuni Hasan; Farikha Aulia; Mohammad Fuad; Imanuelle Tamara Audrey Siampa; Sitti Nailah Rustam; Eka Ernalifia Saputri; Muhammad Aksin Suarso; Radiah Radiah; Nildawati Nildawati; Muhammad Ikhsan; Muhammad Rachmat (Universitas Muhammadiyah Magelang, 2022)
One of the causes of neonatal and infant deaths in Indonesia is vaccine-preventable diseases (PD3I). Since the COVID-19 pandemic, the number of people visiting posyandu (integrated healthcare center) in Bontokassi Village has been reduced. It is probably due to a fear of contracted Covid-19 emerged among the community when coming to posyandu. In addition to low vaccine availability for infants, lack of maternal knowledge is one of the causes of the low vaccination rates among infants in this village. This education was aimed to increase maternal knowledge about the importance of basic immunization for infants to prevent diseases. The result showed increased maternal understanding of the importance of basic immunization after the education program was given.